2023
DOI: 10.1002/adfm.202300941
|View full text |Cite
|
Sign up to set email alerts
|

H2S‐Activated Ion‐Interference Therapy: A Novel Tumor Targeted Therapy Based on Copper‐Overload‐Mediated Cuproptosis and Pyroptosis

Fan Zhao,
Liying Liang,
Heng Wang
et al.

Abstract: Copper overload is a novel way to achieve copper‐ion‐interference therapy by disrupting copper homeostasis and treating diseases through multiple cell death pathways. However, it is difficult to reach copper overload since excess intracellular copper ions will be pumped out. Herein, copper overload is achieved by both raising cellular uptake and reducing the efflux of copper ions using hydrogen sulfide (H2S)‐responsive copper hydroxyphosphate nanoparticles (Cu2(PO4)(OH) NPs). After immersion in an H2S‐enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…It is noteworthy that the targeted design of environmentally responsive nanomedicines can be tailored to the unique TME of different tumors. Zhao et al demonstrated using Cu 2 (PO 4 )­(OH) nanoparticles, capable of converting into CuS nanoparticles within the H 2 S-rich TME of colon cancer . This characteristic maximizes copper ion uptake by the tumor and reduces damage to normal tissues …”
Section: Targeting Cuproptosis: Shooting a Nanodrug Into Achilles’ Heelmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that the targeted design of environmentally responsive nanomedicines can be tailored to the unique TME of different tumors. Zhao et al demonstrated using Cu 2 (PO 4 )­(OH) nanoparticles, capable of converting into CuS nanoparticles within the H 2 S-rich TME of colon cancer . This characteristic maximizes copper ion uptake by the tumor and reduces damage to normal tissues …”
Section: Targeting Cuproptosis: Shooting a Nanodrug Into Achilles’ Heelmentioning
confidence: 99%
“…151 This characteristic maximizes copper ion uptake by the tumor and reduces damage to normal tissues. 151 Nanodrugs Targeting Metabolism. As previously mentioned, the occurrence of cupropostosis is intricately linked to cellular metabolism.…”
Section: Targeting Cuproptosis: Shooting a Nanodrug Into Achilles' Heelmentioning
confidence: 99%
See 2 more Smart Citations
“…[99] By coordinating natural polyphenols and chemically synthesized polyphe-nol derivatives with metal ions, Dai's group constructed a metalpolyphenol coordination nanomedicine PWE, which converted radiation therapy-mediated apoptosis into pyroptosis through epigenetic methods and then stimulated systemic antitumor immune response. [100] Yu et al [101] suggested a copper overload strategy using H 2 S to accumulate copper ions in colon cancer cells. This approach enhances cellular uptake and reduces copper ion efflux, enabling effective and selective treatment of colon cancer through cuproptosis and pyroptosis.…”
Section: Nanosheet Membrane-targeted Photosensitizer and Metal Materi...mentioning
confidence: 99%